Efficacy of inpatient treatment for atopic dermatitis evaluated by changes in serum cortisol levels. Issue 1 (5th October 2012) - Fukuda, Hidetsugu; Suzuki, Taku; Saotome, Atsuko; Sode, Eri; Mukai, Hideki
Abstract When dealing with patients with severe atopic dermatitis (AD), inpatient treatment is useful for alleviating skin symptoms in short periods of time. We previously found that many severe AD patients had low serum cortisol levels at admission. The present study was undertaken to evaluate the efficacy of inpatient treatment in 29 adults with AD through comparisons of serum cortisol, plasma adrenocorticotropic hormone (ACTH), serum thymus and activation‐regulated chemokine (TARC), and serum lactate dehydrogenase (LDH) levels at admission with those at the time of discharge. Serum cortisol and plasma ACTH levels were significantly higher at discharge. On the other hand, serum TARC and serum LDH were significantly lower at discharge. We examined whether the suppression of hypothalamic–pituitary–adrenocortical function that was seen at admission was attributable to disturbed circadian rhythms due to sleep disorders by analyzing hypothalamic–pituitary–adrenocortical function in relation to the presence/absence of sleep disorders, serum cortisol levels and daily urinary free cortisol. Of the 17 patients with low serum cortisol levels upon admission, 15 (88.2%) had sleep disorders upon admission. However, the daily urinary free cortisol increased significantly from 8.0 ± 5.5 μg/day (at admission) to 18.5 ± 17.2 μg/day (at discharge). These results suggested that the suppression of endocrine function seen at admission was not attributable to disturbed circadian rhythms due to sleep disorders but represented true suppression of the endocrine system. These results indicated that inpatient care was useful for treating patients with severe AD, enabling efficient improvement of the skin condition and recovery from suppressed endocrine function.